Acute encephalomyelitis with multiple herpes viral reactivations during abatacept therapy. (9th May 2013) - Nakajima, Hideto; Takayama, Ayami; Ito, Takumi; Yoshikawa, Tetsushi
Abstract : To describe the case of a patient who had been receiving abatacept, a T-cell costimulatory molecule blocker for rheumatoid arthritis, and developed an acute encephalomyelitis associated with reactivation of the varicella zoster virus (VZV), Epstein-Barr virus (EBV) and cytomegalovirus (CMV). A 61-year-old woman receiving abatacept therapy for rheumatoid arthritis developed a disturbance of consciousness. MRI indicated multifocal parenchymal lesions in the brainstem, supratentorial areas and cervical spinal cord. Although steroid therapy significantly improved the neurological symptoms and MRI findings, the patient died of sepsis aggravated by coinfection with a fungal infection. Retrospectively, a PCR assay revealed continued systemic reactivation of VZV, EBV and CMV. Acute encephalomyelitis may be associated with VZV EBV and CMV reactivation during abatacept therapy. Clinicians must be aware of the possibility of acute encephalomyelitis associated with herpes virus reactivation during abatacept therapy for rheumatoid arthritis.